Corticobulbar activity in healthy humans and Parkinson’s disease: a study protocol for a novel biomarker of motivational arousal - Ferraioli, Francesca; Tomaiuolo, Francesco; Falzone, Alessandra M.; Labate, Angelo; Cardali, Salvatore M.; Massimino, Simona; Esposito, Fabrizio; Germanò, Antonino; Trojano, Luigi; Vicario, Carmelo Mario (Frontiers in Psychology, 2025)
BackgroundThe corticobulbar (CB) tract connects the primary motor cortex to oral and facial effectors and may contribute to affective-motivational processes through its interactions with dopaminergic circuits. Prior studies have shown that excitability in the tongue motor cortex (tM1), as well as surface electromyographic (sEMG) activity of submental muscles (SbM), is modulated by hedonic and aversive stimuli. These findings suggest a potential role for the CB system as a physiological interface between motivational states and motor expression.ObjectivesThis protocol explores whether CB excitability can serve as an indirect marker of motivational arousal in both healthy individuals and patients with Parkinson’s disease (PD), a condition marked by dopaminergic dysfunction.MethodsStudy 1 protocol consists in a virtual reality-based shopping task where healthy adults (n = 100) are asked to do different food shipping based on motivational-affective value, while their SbM EMG activity is recorded. Study 2 assesses CB excitability via SbM motor evoked potentials (MEPs) in PD patients (n = 15) before and after a 3-month period of dopaminergic therapy (levodopa), and across ON/OFF medication states. The study design includes a control group (n = 15) tested twice, after a 3-month period, without any drug or placebo administration. Behavioral and self-report measures related to motivation and reward sensitivity are also included in both studies.ConclusionThis protocol combines advanced neurophysiological techniques with innovative experimental paradigms to investigate CB tract cortical excitability linkage with reward-related processing. By integrating neurophysiological, behavioral, and pharmacological measures, this protocol aims to clarify whether CB excitability reflects motivational and dopaminergic states. Findings may contribute to identifying non-invasive biomarkers of motivational functioning in both clinical and normative populations.